A shotcrete modifier and its preparation method and application
By using spray concrete modifiers composed of metakaolin and anhydrous gypsum, the aluminum phase components are stimulated to generate ettringite, which solves the problem of insufficient volume stability and sulfate resistance resistance of spray concrete, and achieves significant early strength Improved and improved crack and seepage resistance.
Patent Information
- Application Number
- CN202310149355.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-22
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-02-22
AI Technical Summary
The existing spray concrete has shortcomings in volume stability and sulfate resistance, and the specific surface area of metakaolin cannot be effectively controlled to replace the role of fume, resulting in the concrete being prone to cracking and poor sulfate resistance.
Using spray concrete modifiers composed of metakaolin, anhydrous gypsum, organic components and inorganic nanomineral powder, the aluminum phase components are stimulated to produce ettringite, which improves early strength and sulfate resistance, and reduces the components. and consistency modifiers reduce rebound and dry shrinkage.
The volume stability of sprayed concrete is significantly improved, the risk of concrete cracking is reduced, early strength and compactness is increased, and sulfate resistance is improved.
Smart Images

Figure CN116283036B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a shotcrete modifier and a preparation method and application thereof. Background Art
[0002] Shotcrete is a type of concrete that is sprayed and poured with a pressure spray gun. It is often used to pour tunnel support linings, thin-walled structures such as walls and ceilings, or other structural linings, and protective layers of steel structures. Since shotcrete does not require formwork or vibration, construction is fast and convenient, and it is widely used in many fields such as water conservancy and hydropower, slope support, mining development, underground engineering, and engineering reinforcement. However, shotcrete generally has disadvantages such as high rebound rate, long setting time, low early strength, thin thickness of one spraying, and poor compactness. Currently, commonly used technical measures include adding silica fume (also known as silica powder, microsilica powder), nano-SiO2 and other admixtures and chemical admixtures such as water reducers and viscosity enhancers, which effectively shorten the initial and final setting time of shotcrete, reduce the rebound rate, and improve the strength and compactness. However, while this type of active silica admixture improves the performance of shotcrete, it also causes an increase in the self-shrinkage and shrinkage of concrete, reduces the volume stability of concrete, and increases the risk of concrete cracking.
[0003] As an industrial recycling material, silica fume has unstable quality and limited sources, while kaolin is a mineral admixture with abundant resources, industrial production and controllable quality. When controlled at a higher specific surface area, it has similar volcanic ash activity as silica fume. The main active components of kaolin are amorphous Al2O3 and SiO2, which can react with cement hydration product Ca(OH)2 to generate different secondary hydration products, including tobermorite, hydrated calcium aluminum feldspar, hydrated tetracalcium aluminate and hydrated tricalcium aluminate. Kaolin has been widely used in existing concrete modification technology. For example, Chinese patent CN113321474A announced the Chinese invention patent "An impermeable shotcrete". Kaolin is only used as an admixture in the shotcrete. The invented shotcrete has the advantages of good impermeability and high compressive strength. Chinese patent CN112441760A discloses a composite admixture for shotcrete and its preparation method and application. Metakaolin is one of the components of the composite admixture, and the prepared shotcrete has a significantly reduced rebound rate. Chinese patent CN110104987A discloses a high early strength alkali-free liquid accelerator and its preparation method and application. Metakaolin is one of the accelerating components of the invention, which greatly improves the accelerating effect of the alkali-free liquid accelerator and reduces the dosage of the alkali-free liquid accelerator. Chinese patent CN108483977A discloses a method for preparing a shotcrete modifier for coal mine tunnels, which utilizes the heat in the cooling process after calcining metakaolin to stimulate the reaction between carboxymethyl cellulose and polyvinyl alcohol, and simultaneously utilizes water evaporation to quickly cool the metakaolin, thereby forming a method for preparing a shotcrete modifier for coal mine tunnels that has both strengthening and increasing adhesion. Chinese patent CN102826774A discloses a nano-scale shotcrete modified admixture, in which metakaolin is used as one of the mineral admixtures, which may or may not be added in the embodiments. The invention can reduce the rebound and setting time of shotcrete and increase the thickness of a spray layer.
[0004] However, in the above-mentioned prior art, kaolin is used to improve the strength, impermeability and durability of shotcrete, reduce the rebound rate, etc., and the performance in improving the volume stability of shotcrete and reducing the risk of concrete cracking is not reflected, and the specific surface area of kaolin is not controlled or controlled at a low value, and it cannot replace silica fume. At the same time, due to the limited SO3 content in cement, the aluminum phase component in kaolin only reacts with the cement hydration product Ca(OH)2 to generate different aluminates, and cannot be fully stimulated and utilized to further generate calcium sulfonate that can improve the volume stability of concrete; when the shotcrete that has been hydrated and matured to form structural strength is in a corrosive environment with sulfate, the sulfate invading from the outside will react with the aluminum phase that has not been fully stimulated to regenerate calcium sulfonate, which will generate expansion stress and crack damage, thereby reducing the sulfate resistance and durability of the shotcrete. Summary of the invention
[0005] In view of the shortcomings of current shotcrete modifiers, the present invention provides a shotcrete modifier and a preparation method and application thereof, which are mainly used to improve the volume stability of shotcrete and reduce the risk of concrete cracking. At the same time, it can significantly reduce rebound, increase early strength and density, and improve the sulfate resistance and durability of shotcrete.
[0006] In order to achieve the above technical objectives, the present invention adopts the following scheme:
[0007] A shotcrete modifier, comprising the following components in parts by weight:
[0008] 50-70 parts of metakaolin, 20-30 parts of activating component, 10-20 parts of shrinkage reducing component, 1.5-2 parts of water reducing agent, 0.2-0.5 parts of consistency modifier, 1-2 parts of setting adjusting component;
[0009] The exciting component is anhydrous gypsum, the shrinkage reducing component is composed of organic components and inorganic nano-mineral powder, and the organic component is one or both of dipropylene glycol monomethyl ether and polyethylene glycol monomethyl ether.
[0010] As a preferred embodiment, the metakaolin has a specific surface area of 10000 to 15000 m 2 / kg, wherein the total content of Al2O3 and SiO2 is greater than 85%. The metakaolin not only has high hydration activity, but also has better dispersibility and workability than silica fume.
[0011] As a preferred embodiment, the anhydrous gypsum has a specific surface area of 400 to 600 m 2 / kg, composed of one or more of natural anhydrite and calcined gypsum; the calcined gypsum is desulfurized gypsum calcined at 800°C and kept warm for 1h before being ground to a specific surface area of 400-600m 2 / kg. The use of anhydrous gypsum as an activator can fully activate the aluminum phase components in the kaolin to generate ettringite with expansion effect, which can not only compensate for the shrinkage of concrete and improve the early strength, but also improve the sulfate resistance of shotcrete.
[0012] As a preferred embodiment, the mass ratio of the organic component to the inorganic nano-mineral powder in the shrinkage-reducing component is 1:5 to 10. The shrinkage-reducing component is a powder, and the nano-mineral powder is used as a carrier of the shrinkage-reducing organic component, does not contain an organic solvent, and can be conveniently used in the preparation of the modifier.
[0013] As a preferred embodiment, the organic component is a mixture of dipropylene glycol monomethyl ether and polyethylene glycol monomethyl ether in a mass ratio of 3:3 to 7.
[0014] As a preferred implementation, the inorganic nano-mineral powder is nano-limestone powder with a particle size of ≤100nm.
[0015] As a preferred embodiment, the water reducing agent is a polycarboxylic acid-based or naphthalene-based water reducing agent, and the water reducing rate is ≥25%.
[0016] As a preferred embodiment, the consistency modifier is composed of one or two of cellulose derivatives, degraded starch and its derivatives in a mass ratio of 1:3 to 5.
[0017] As a preferred embodiment, the setting component is one or a combination of phosphate, citric acid and sucrose.
[0018] Another object of the present invention is to provide a method for preparing the above concrete modifier, which comprises the following steps:
[0019] (1) adding the organic component in the shrinkage-reducing component into deionized water and stirring to completely dissolve it to obtain an organic component solution;
[0020] (2) uniformly mixing the inorganic nano-mineral powder with the organic component solution, and then spray drying to obtain a shrinkage-reducing component;
[0021] (3) Adding kaolin, an activating component, a shrinkage reducing component, a water reducing agent, a consistency modifier, and a setting regulating component according to weight parts into a mixer and stirring for 8 to 10 minutes, and mixing evenly to obtain the shotcrete modifier.
[0022] Another object of the present invention is to provide an application of the above-mentioned shotcrete modifier in shotcrete modification, characterized in that the shotcrete modifier is used to replace cement in the shotcrete at a dosage of 15% to 20%.
[0023] The metakaolin used in the present invention has a specific surface area of 10000 to 15000m 2 / kg, the total content of amorphous Al2O3 and SiO2 active crystals> 85%, and the specific surface area of the excited components is 400-600m 2 / kg, which ensures the high chemical activity of kaolin as a fine powder, and has better dispersibility and workability than silica fume. The highly active Al2O3 and SiO2 components in kaolin react with Ca(OH)2 in the cement hydration system to generate more compact calcium silicate hydrate and calcium aluminate hydrate. The calcium aluminate hydrate is further stimulated by the sulfate of the stimulating component to generate calcium sulfonate. The formation of calcium sulfonate significantly improves the early strength of shotcrete, and its volume expansion can compensate for the partial shrinkage of shotcrete, thereby improving the volume stability of shotcrete. Since the hydration activity of the aluminum phase in kaolin is fully stimulated, the sulfate resistance of shotcrete is also improved. At the same time, the physical adsorption of the fine powder of kaolin increases the cohesion and adhesion of shotcrete, thereby reducing the rebound rate.
[0024] The shrinkage-reducing component in the modifier can effectively reduce the drying and self-drying shrinkage of concrete by reducing the surface tension of water in the capillaries of cement stone, and is not easily affected by construction and maintenance conditions, thereby significantly improving the volume stability of shotcrete and reducing the risk of concrete cracking. On the one hand, the nano-limestone powder in the shrinkage-reducing component can be used as a carrier of the shrinkage-reducing organic component to ensure the uniformity of the shrinkage-reducing component in the modifier, and can also increase the cohesion of the shotcrete and reduce rebound; on the other hand, nano-calcium carbonate can stabilize the generated ettringite, prevent it from transforming into a low-sulfur type, and avoid a decrease in strength in the later stage.
[0025] The setting-regulating components and thickening components in the modifier give wet shotcrete good plasticity and adhesion, further reducing concrete rebound.
[0026] After adding 15% to 20% of the shotcrete modifier of the present invention, compared with the shotcrete added with 10% silica fume, the rebound rate of the shotcrete is reduced to below 7%, the 60d shrinkage value can be reduced by more than 50%, the 1d compressive strength can be increased by more than 45%, the 28d compressive strength is increased by more than 14%, and the water seepage height is reduced by more than 70% under a water pressure of 2.0MPa.
[0027] The sprayed concrete modifier of the present invention can significantly improve the volume stability of sprayed concrete and reduce the risk of concrete cracking. At the same time, the rebound rate of the sprayed concrete is significantly reduced, and the early strength and density are significantly increased, which significantly improves the crack resistance and anti-seepage performance of the sprayed concrete, and the sulfate resistance and durability are also improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is the drying shrinkage curve diagram of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION
[0029] In order to better understand the present invention, the following examples are provided to further illustrate the present invention and should not be considered as any form of limitation to the present invention.
[0030] The sprayed concrete foundation mix ratios used in the embodiments and comparative examples are shown in Table 1 (unit: kg / m 3 ):
[0031] Table 1 Shotcrete foundation mix ratio
[0032] cement sand Stone Water reducing agent water Accelerator 475 912 762 6.65 190 28.5
[0033] Raw materials:
[0034] Cement: P.O42.5; Sand: natural river sand, fineness modulus 2.65; Gravel: 5-15mm crushed stone; Water reducer: polycarboxylic acid water reducer, water reduction rate 27%; Accelerator: alkali-free accelerator.
[0035] Using the wet spraying process, 20% of the modifier was added to the cements of Examples 1-2, 15% of the modifier was added to the cements of Examples 3-5 and Comparative Examples 1-2, and 10% of silica fume was added to the cement of Comparative Example 3.
[0036] Example 1
[0037] A shotcrete modifier is prepared by mixing the following components in parts by weight:
[0038] 50 parts of metakaolin, 30 parts of activating component, 20 parts of shrinkage reducing component, 1.5 parts of water reducing agent, 0.5 parts of consistency modifier, and 2 parts of setting component.
[0039] Among them, the specific surface area of kaolin is 15000m 2 / kg, the exciting component is calcined gypsum, with a specific surface area of 500m 2 / kg; the shrinkage reducing component is composed of polyethylene glycol monomethyl ether and inorganic nano-mineral powder mixed in a ratio of 1:10; the consistency modifier is composed of hydroxypropyl cellulose and hydroxypropyl starch ether mixed in a ratio of 1:5; the setting component is phosphate.
[0040] The preparation method is as follows: an organic component (polyethylene glycol monomethyl ether) is added to deionized water to prepare a 10-20 (w / w) organic component solution, and then inorganic nano-mineral powder is added to the organic component solution according to a mass ratio, mixed evenly, and then spray-dried to obtain a shrinkage-reducing component.
[0041] Weigh kaolin, activating component, shrinkage reducing component, water reducing agent, consistency modifier and setting regulating component according to mass, pour the weighed components into a mixer, add the materials in no particular order, stir for 8 to 10 minutes, and mix evenly to obtain the shotcrete modifier.
[0042] Example 2
[0043] A shotcrete modifier is prepared by mixing the following components in parts by weight:
[0044] 55 parts of metakaolin, 25 parts of activating component, 20 parts of shrinkage reducing component, 1.5 parts of water reducing agent, 0.5 parts of consistency modifier, and 1.5 parts of setting component.
[0045] Among them, the specific surface area of kaolin is 12500m 2 / kg, the exciting component is anhydrite, with a specific surface area of 500m 2 / kg; the organic component in the shrinkage reducing component is composed of dipropylene glycol monomethyl ether and polyethylene glycol monomethyl ether in a ratio of 3:7, and the organic component and inorganic nano-mineral powder are mixed in a mass ratio of 1:10 to obtain the shrinkage reducing component; the consistency modifier is composed of hydroxypropyl cellulose and hydroxypropyl starch ether in a ratio of 1:4; the setting component is sucrose.
[0046] Example 3
[0047] A shotcrete modifier is prepared by mixing the following components in parts by weight:
[0048] 70 parts of metakaolin, 20 parts of activating component, 10 parts of shrinkage reducing component, 2 parts of water reducing agent, 0.2 parts of consistency modifier and 1 part of setting component.
[0049] Among them, the specific surface area of kaolin is 12500m 2 / kg, the exciting component is natural anhydrite, with a specific surface area of 500m 2 / kg; the shrinkage reducing component is a mixture of polyethylene glycol monomethyl ether and inorganic nano-mineral powder in a mass ratio of 1:5; the consistency modifier is hydroxypropyl starch ether; and the setting component is sucrose.
[0050] Example 4
[0051] A shotcrete modifier is prepared by mixing the following components in parts by weight:
[0052] 65 parts of metakaolin, 25 parts of activating component, 10 parts of shrinkage reducing component, 2 parts of water reducing agent, 0.3 parts of consistency modifier, and 1.5 parts of setting component.
[0053] Among them, the specific surface area of kaolin is 12500m 2 / kg, the exciting component is natural anhydrite, with a specific surface area of 400m 2 / kg; the organic component in the shrinkage reducing component is composed of dipropylene glycol monomethyl ether and polyethylene glycol monomethyl ether in a mass ratio of 1:1, and the organic component and inorganic mineral powder are mixed in a mass ratio of 1:5; the consistency modifier is a mixture of hydroxypropyl cellulose and hydroxypropyl starch ether in a ratio of 1:3; the setting component is sucrose.
[0054] Example 5
[0055] A shotcrete modifier is prepared by mixing the following components in parts by weight:
[0056] 60 parts of metakaolin, 30 parts of activating component, 10 parts of shrinkage reducing component, 2 parts of water reducing agent, 0.4 parts of consistency modifier and 1.5 parts of setting component.
[0057] Among them, the specific surface area of kaolin is 10000m 2 / kg, the exciting component is calcined gypsum, with a specific surface area of 600m 2 / kg; the organic component in the shrinkage reducing component is composed of dipropylene glycol monomethyl ether and polyethylene glycol monomethyl ether in a mass ratio of 2:3, and the organic mixture is mixed with inorganic mineral powder in a mass ratio of 1:5; the consistency modifier is a mixture of hydroxypropyl cellulose and hydroxypropyl starch ether in a mass ratio of 1:4; the setting component is citric acid.
[0058] Comparative Example 1
[0059] Select modified admixtures without shrinkage-reducing components to test the performance of shotcrete as a comparative example:
[0060] 75 parts of metakaolin, 25 parts of activating component, 2 parts of water reducing agent, 0.5 parts of consistency modifier, and 1.5 parts of setting component.
[0061] Among them, the specific surface area of kaolin is 500m 2 / kg, the exciting component is anhydrite, with a specific surface area of 350m 2 / kg; the consistency modifier is a mixture of hydroxypropyl cellulose and hydroxypropyl starch ether in a ratio of 1:3; the setting component is sucrose.
[0062] Comparative Example 2
[0063] The modified admixture without excitation components was selected to test the performance of shotcrete as a comparative example:
[0064] 80 parts of metakaolin, 20 parts of shrinkage reducing component, 2 parts of water reducing agent, 0.5 parts of consistency modifier, and 1.5 parts of setting regulating component.
[0065] Among them, the specific surface area of kaolin is 12500m 2 / kg; the organic component in the shrinkage reducing component is composed of dipropylene glycol monomethyl ether and polyethylene glycol monomethyl ether in a mass ratio of 1:1, and the organic component and inorganic nano-mineral powder are mixed in a ratio of 1:10 to obtain the shrinkage reducing component; the consistency modifier is composed of hydroxypropyl cellulose and hydroxypropyl starch ether in a ratio of 1:3; the setting component is sucrose.
[0066] Comparative Example 3
[0067] Nano silicon powder was selected as admixture to test the performance of shotcrete as a comparative example:
[0068] 99 parts of nano silicon powder and 1 part of water reducing agent.
[0069] The specific surface area of nano silicon powder is 21000m 2 / kg.
[0070] The modifiers obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were used to conduct comparative tests on working performance, strength performance, impermeability and shrinkage deformation performance. The test method was determined in accordance with the requirements of SL 352-2020 "Testing Procedures for Hydraulic Concrete" and JGJ / T372-2016 "Technical Specifications for Application of Shotcrete". The water seepage height is the water seepage height of the shotcrete specimen tested at a constant pressure of 2.0 MPa water pressure for 24 hours. The performance test results are shown in Tables 2 and Figure 1 .
[0071] Table 2 Performance test results of embodiments and comparative examples
[0072]
[0073] Table 2 and Figure 1 The performance test results show that when the technical parameters of the specific surface area of metakaolin do not meet the characteristic requirements of the present invention, the rebound rate, strength performance, and impermeability of Comparative Example 1 compared with Comparative Example 3 of shotcrete added with silica fume do not reach the performance of shotcrete added with silica fume, and only the shrinkage is slightly smaller; when the modifier has no excitation component, the performance of Comparative Example 2 compared with other embodiments is not as good as that of the embodiment, especially the early strength is significantly lower, and the anti-sulfate durability is also significantly reduced because the aluminum phase is not fully excited. Compared with Comparative Example 3, i.e. the commonly used silica fume shotcrete, after adding 15% to 20% of the shotcrete modifier of the present invention, the rebound rate of the shotcrete is reduced to less than 7%, the 60d shrinkage value can be reduced by more than 50%, the 1d compressive strength can be increased by more than 45%, the 28d compressive strength is increased by more than 14%, the water seepage height is reduced by more than 70% under a water pressure of 2.0MPa, and the anti-sulfate durability is also improved. The shotcrete modifier of the present invention significantly improves the volume stability of shotcrete and reduces the risk of concrete cracking. At the same time, the rebound rate of the shotcrete is significantly reduced, the early strength and density are significantly increased, the crack resistance and anti-seepage performance of the shotcrete are significantly improved, and the sulfate resistance and durability are also improved.
Claims
1. A shotcrete modifier, characterized in that: It is composed of the following components by mass: 50~70 parts of metakaolin, 20~30 parts of stimulating component, 10~20 parts of shrinkage reducing component, 1.5~2 parts of water reducing agent, 0.2~0.5 parts of consistency modifier, 1~2 parts of setting adjusting component; Wherein, the exciting component is anhydrous gypsum, the shrinkage reducing component is composed of organic components and inorganic nano-mineral powder, and the organic component is one or two of dipropylene glycol monomethyl ether and polyethylene glycol monomethyl ether; The specific surface area of the metakaolin is 10000~15000 m 2 / kg, of which the total content of Al2O3 and SiO2>85%; The anhydrous gypsum has a specific surface area of 400-600m 2 / kg, composed of one or more of natural anhydrite and calcined gypsum; the calcined gypsum is desulfurized gypsum calcined at 800°C and kept warm for 1h before being ground to a specific surface area of 400-600m 2 / kg.
2. The sprayed concrete modifier according to claim 1, characterized in that The mass ratio of the organic component to the inorganic nano-mineral powder in the shrinkage-reducing component is 1:5-10.
3. The sprayed concrete modifier according to claim 1, characterized in that The inorganic nano mineral powder is nano limestone powder with a particle size of ≤100nm.
4. The sprayed concrete modifier according to claim 1, characterized in that The water reducing agent is a polycarboxylic acid-based or naphthalene-based water reducing agent, and the water reducing rate is ≥25%.
5. The sprayed concrete modifier according to claim 1, characterized in that The consistency modifier is composed of one or two of degraded starch and its derivatives and cellulose derivatives in a mass ratio of 1:3-5.
6. The sprayed concrete modifier according to claim 1, characterized in that: The coagulation regulating component is one or a combination of phosphate, citric acid and sucrose.
7. The method for preparing the sprayed concrete modifier according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) adding the organic component in the shrinkage-reducing component into deionized water and stirring to completely dissolve it to obtain an organic component solution; (2) uniformly mixing the inorganic nano-mineral powder and the organic component solution, and then spray drying to obtain a shrinkage-reducing component; (3) Adding kaolin, an activating component, a shrinkage reducing component, a water reducing agent, a consistency modifier, and a setting regulating component according to parts by mass into a mixer and stirring for 8 to 10 minutes until the mixture is evenly mixed to obtain the shotcrete modifier.
8. Use of the sprayed concrete modifier according to any one of claims 1 to 6 in sprayed concrete modification, characterized in that: The shotcrete modifier is used to replace cement in shotcrete at a dosage of 15% to 20%.